Political Branding Analysis of @Gibran_Rakabuming Tiktok Accounts during the 2024 Presidential Election Campaign - Merlyana Ryandaresta; Muhammad Thoyib Amali (Publikasi Indonesia, 2024)
Social media, especially TikTok, is a platform that is currently used for political campaigns. Ahead of the 2024 Presidential Election, talks about presidential candidates and vice presidential candidates, especially Gibran, are increasingly being discussed in various media. The many pros and cons that have arisen among the public regarding the candidacy of Gibran Rakabuming Raka as a vice presidential candidate have become the culmination of the polemic. This study aims to analyze the political branding of TikTok @gibran_rakabuming accounts during the 2024 presidential election campaign. This research method uses a descriptive qualitative method and is analyzed using theories from Gelder and Sonies which consists of three indicators, namely, appearance, personality, and key political messages. Case studies on TikTok accounts @gibran_rakabuming were taken during the period from November 28, 2023, to February 10, 2024. The results of the research show that Gibran has successfully used the TikTok platform to build an image as a vice presidential candidate who is ready to bring positive changes to Indonesia with a relevant, close to the community, and adaptive to technological developments and the needs of the community, especially the younger generation. The use of social media platforms such as TikTok is also a powerful strategy to reach young people and make them candidates who not only talk about the future but also invite the public to work together to realize a more advanced Indonesia.